Potassium Metal Batteries: Stable Potassium Metal Anodes with an All‐Aluminum Current Collector through Improved Electrolyte Wetting (Adv. Mater. 49/2020). Issue 49 (8th December 2020) - Liu, Pengcheng; Wang, Yixian; Hao, Hongchang; Basu, Swastik; Feng, Xuyong; Xu, Yixin; Boscoboinik, Jorge Anibal; Nanda, Jagjit; Watt, John; Mitlin, David
Abstract : An explorer is kayaking in uncharted territory, representing the exciting scientific pursuit of emerging metal batteries (MBs). Water is flowing smoothly over the jagged rocks, representing dendrite‐free metal anodes as well as enhanced electrolyte wetting, both due to geometrical roughness. The electric eels underneath represent potassium‐based energy storage, as they utilize potassium and sodium ions for electricity. In article number 2002908, Pengcheng Liu, David Mitlin, and co‐workers present a route via improved electrolyte wetting toward stable potassium metal batteries with an all‐aluminum current collector.